Hubungan Pengetahuan Tentang Gizi Dengan Kejadian Anemia Pada Wanita Usia Subur di Wilayah Puskesmas Bangkingan Surabaya - Tsanir Rohmah Zamzami Ninik; Astuti Setiyani; Novita Eka Kusuma Wardani; Rodiyatun (Gema Bidan Indonesia, 2023)
During the period of women of childbearing age there are many health problems, one of which is anemia. Anemia is a condition where the hemoglobin level is less than the normal value according to the age group (≤ 12 g/dl for WUS). The purpose of this study was to determine the relationship between knowledge about nutrition and the incidence of anemia in women of childbearing age (WUS). This type of research is an analytical survey with the Cross Sectional method. The population of Women of Reproductive Age (WUS) is 310 respondents with a sample using the Purposive Sampling technique of 122 respondents. Data collection was processed using the Spearman Rho statistical test with an α value of 0.05. Nearly half of the respondents (WUS) had good knowledge of nutrition (52%) and only a small proportion, namely 15 (12.3%) had anemia. The results of the Spearman Rho statistical test obtained a significance value of p = 0.022. So H1 is accepted. The results of the analysis concluded that there was a relationship between nutritional knowledge and the incidence of anemia in (WUS). There is a relationship between nutritional knowledge and the incidence of anemia in (WUS). So it is recommended for Women of Reproductive Age (WUS) to continue to increase knowledge about nutrition through ways and by utilizing easily accessible multimedia Keywords: knowledge, nutrition, anemia